2023
DOI: 10.3390/land12081514
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Disaster Management Systems: Approaches, Challenges, and Future Directions

Saad Mazhar Khan,
Imran Shafi,
Wasi Haider Butt
et al.

Abstract: Disaster management is a critical area that requires efficient methods and techniques to address various challenges. This comprehensive assessment offers an in-depth overview of disaster management systems, methods, obstacles, and potential future paths. Specifically, it focuses on flood control, a significant and recurrent category of natural disasters. The analysis begins by exploring various types of natural catastrophes, including earthquakes, wildfires, and floods. It then delves into the different domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 124 publications
1
8
0
Order By: Relevance
“…In many instances, communities that are vulnerable to adverse climate change events are also disproportionately affected by food insecurity [34,109,110]. Consistent with existing literature [40,[50][51][52][53], this review found that digital apps, particularly those which provide real-time alerts, information, and communication, can not only ensure that solutions are catered to communities' specific needs, but also foster a sense of empowerment among community members [83,84,92].…”
Section: Connecting Climate Change With Food Security and Mental Heal...supporting
confidence: 71%
See 1 more Smart Citation
“…In many instances, communities that are vulnerable to adverse climate change events are also disproportionately affected by food insecurity [34,109,110]. Consistent with existing literature [40,[50][51][52][53], this review found that digital apps, particularly those which provide real-time alerts, information, and communication, can not only ensure that solutions are catered to communities' specific needs, but also foster a sense of empowerment among community members [83,84,92].…”
Section: Connecting Climate Change With Food Security and Mental Heal...supporting
confidence: 71%
“…Capturing the intersection of these complex global health issues requires leveraging existing and emerging technology [50][51][52]. Digital applications (apps) have long been used to track changing weather patterns and climate events [40,53] but the increasing frequency and severity of climate change warrants citizen engagement and participation to better understand both specific impacts, as well as targeted solutions in the age of climate emergency [1,5,12]. Citizen science has a longstanding history of citizen engagement to capture local environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The KTB, a new boosting ML model introduced in 2021, presented a high potential in learning and predicting complex data with similar performance to the CB model (R 2 = 0.86). Boosting was found to outperform the bagging and SVM groups in the retrieval of both classification and bio-physical parameters [27,50,51,61] with advancements in algorithm structures and the creative workflow in the decision making of the final model [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of debris flow disaster mitigation, numerical technologies play a crucial role in disaster prevention [13,14]. Many studies focus on numerically solving the Navier-Stokes (N-S) equation.…”
Section: Introductionmentioning
confidence: 99%